Importance of sensory evaluation in assessment of egg quality - Margeta, Polona (Array, 2019)
The sensory evaluation is a scientific discipline used to evoke, measure, analyze and interpret reactions to stimuli perceived through senses of sight, smell, touch, taste, and hearing. Sensory evaluation applies principles of experimental design and statistical analysis to the use of human senses aiming to isolate the sensory properties of foods themselves and provide important and useful information to product developers, food scientists, and managers about the sensory characteristics of food products. To achieve the scientific control of the sensory evaluation test, good laboratory practice should be applied. It includes defining the test objective and test type, selection of right assessors, ensuring right test area, handling and preparing the sample in appropriate way, paying attention to test set-up and storing the test data safe in logical order. Regarding eggs, sensory characteristics are usually evaluated on eggs enriched with bioactive compounds. Sensory studies are often conducted either with trained (in accordance with international reference standards) or untrained panelists. Sensory evaluation of eggs after addition of different compounds is of great importance because sensory attributes such as aroma, flavor, aftertaste and overall acceptability of enriched eggs are very important to consumers.